The Cipriano Cid Memorial Library at the U.P. Institute of Industrial Relations user needs and information-seeking behavior - Magday, Edralin O.; Atienza, Daisy B.; Aganon, Marie E. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1986)
Delivery of effective information services is not possible without the identification and assessment of the users' information needs and their information-seeking behavior patterns. This study was designed to identify the information needs and information-seeking behavior of the users of the CCM Library of the Institute of Industrial Relations, University of the Philippines. The main purpose of this study was to make recommendations for the CCM Library to enable it to render better service to its users. The specific objectives are: 1) To identify information-seeking behavior pattern of different types of users of the CCM Library; 2) To ascertain the users' awareness of the information services provided and which of these they prefer; 3) To know how users perceive the services rendered by the CCM Library staff; and 4) To highlight some problem areas and recommendations to improve the information services of the CCM Library.
A comprehensive questionnaire consisting of twenty five items was developed and refined after pretests were conducted with two sample of questionnaires from each group of respondents. The refined questionnaire was distributed to 27 trade unionists based in Quezon City who were either enrollees or seminar participants in the IIR during the previous semesters, 12 faculty, 8 training specialists, 70 students and 7 researchers of the Institute of Industrial Relations during the second semester of academic year 1984-85. Out of the 124 questionnaires distributed, only 95 (23 from the trade unionists, 12 from the faculty, 8 from the training specialists, 45 from the students and 7 from the researchers) were returned and were analyzed, tabulated and interpreted. Percentages, averages and cross tabulations were used in the analysis of data. Simple tallies of frequencies of the responses that could be dichotomized into Yes/No responses were also done. The responses to items that do not demand rating or ranking were tallied and the frequency of such category of responses were noted. Items that demand ranking of the responses were assigned scores according to the rank given. For some other questions, percentages were calculated.
The major findings of the study positively confirmed the hypotheses which were formulated as follows: 1) Users' need for certain types of information are very much related to the role/functions they perform in their organizations and society.2) The U.P. Industrial Relations faculty, students, training specialists, researchers, and trade unionists are equally aware of the information services, resources and facilities of the CCM Library.3) The different types of users of the CCM Library use very similar methods and sources in seeking information.4) The U.P Industrial Relations faculty, students, training specialists, researchers and trade unionists perceived the CCM Library services satisfactorily.
Based on the findings, the following conclusions were drawn:1) User's need for certain types of information are much related to the role/functions they perform in their organizations and society.2) The U.P. Industrial Relations faculty, students, training specialists, researchers, and trade unionists are equally aware of the information services, resources, and facilities of the CCM Library.3) The different types of users of the CCM Library use very similar methods and sources in seeking information.4) The U.P. Industrial Relations faculty, students, training specialists, researchers, and trade unionists perceived the CCM Library services satisfactory.
To achieve a high degree of library use and satisfaction in the use of the CCM Library, its resources and facilities, the following recommendations were offered:1) A copy of this study should be furnished to management of the U.P. Institute of Industrial Relations and the University Library for further study towards a review of the library programs and policies necessary to suit the ever increasing and changing demands of the users.2) Additional budget from the library book fund is recommended and additional local support is needed to maintain adequate services for the graduate, training and research programs of the institute.3) In view of the seeming over reliance on the librarian especially by the faculty and the students in the pursuit of their library and information needs, it is recommended that the CCML librarian be encouraged to avail of training in Industrial Relations as well as updating courses on library management of industrial relations libraries in order to develop that kind of professionalism for the job. This way, the librarian can be more responsible to the needs of the library and its users.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman). -- Institute of Industrial Relations; Information services; Library use studies